How to write an investment policy statement - DiBruno, Rocco (Wiley, 2013)
An indispensable resource for every financial service professionals developing an IPS The Investment Policy Statement (IPS) is one of the most critical documents fiduciaries must draft. For years, ERISA and other industry regulations have governed the guidelines all fiduciaries must comply with when drafting one. But the current climate of corporate scandal and the 2008 global banking crisis have led to increased scrutiny by regulators, prompting firms to take a closer look at the quality and integrity of their IPSs and to take steps to have a rigorous formal process in place.